2014
DOI: 10.1364/boe.5.004417
|View full text |Cite
|
Sign up to set email alerts
|

Engineering optically triggered droplets for photoacoustic imaging and therapy

Abstract: Liquid perfluorocarbon (PFC) droplets incorporating optical absorbers can be vaporized through photothermal heating using a pulsed laser source. Here, we report on the effect of droplet core material on the optical fluence required to produce droplet vaporization. We fabricate gold nanoparticle templated microbubbles filled with various PFC gases (C 3 F 8 , C 4 F 10, and C 5 F 12 ) and apply pressure to condense them into droplets. The core material is found to have a strong effect on the threshold optical flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 36 publications
(50 reference statements)
4
56
1
Order By: Relevance
“…Several studies have confirmed that the ADV threshold can be as high as 5 MPa, while several PA droplet formulations require up to a 400 mJ/cm 2 laser fluence for activation 14,18,27,28,3639 . In many cases, the pressures and optical fluences required to initiate droplet vaporization approach exceed FDA and ANSI limits for diagnostic purposes.…”
mentioning
confidence: 99%
“…Several studies have confirmed that the ADV threshold can be as high as 5 MPa, while several PA droplet formulations require up to a 400 mJ/cm 2 laser fluence for activation 14,18,27,28,3639 . In many cases, the pressures and optical fluences required to initiate droplet vaporization approach exceed FDA and ANSI limits for diagnostic purposes.…”
mentioning
confidence: 99%
“…As the area is continually irradiated, more nanoparticles are vaporized, creating a cascading effect of tumor destruction and deeper penetration. Combining laser and ultrasound irradiation can also be used to facilitate PFC droplet vaporization, enhancing the tissue penetration of the nanoparticles [63][64][65]. The therapeutic effects of PTT here are amplified due to enhanced distribution of SPIO and DIR throughout the tumor compared to existing nanomedicine therapies that rely on the EPR effect alone.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been proposed that even greater contrast enhancement in photoacoustic imaging could be achieved through the use of volatile droplets whose vaporization is triggered by light. 2,8,9 However, the necessary phase change consumes energy under the form of latent heat, that cannot then participate in the acoustic generation, which makes the use of the available energy inherently suboptimal. Stable microbubbles modified with the addition of an optically absorbing coating have been proposed as a potential solution to this problem.…”
Section: Introductionmentioning
confidence: 99%